Quality of water supply for a slaughterhouse in the municipality of Castanhal, Pará (Research, Society and Development, 2021)
Supply water is a fundamental resource in slaughterhouses that make use of water in various operations, whether in direct or indirect contact with the products. This study aimed to evaluate the quality parameters of the water supply for a slaughterhouse of bovine slaughterhouses, located in the municipality of Castanhal, in the state of Pará. For this, the water samples were collected in three different points, being obtained samples in the slaughtering, giblets and poultry sector. The physicochemical (free residual chlorine, apparent color, pH and turbidity) and microbiological (total coliforms and coliforms at 45 ° C) characteristics were evaluated during the period from January to December 2019. The results showed that all physical-chemical and microbiological parameters of the analyzed samples remained within the standards required by the Ministry of Health. These results may reflect the water treatment that the slaughterhouse uses, which consists of the steps of pH correction, flocculation, coagulation, filtration and chlorination.